Awareness and Utilization of Artificial Intelligence Among Secondary School Biology Students in Lere, Kaduna State - Musa, Hauwa Rabiu; Adamu, Arome Tairu; Nuru, Ramatu Asabe (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study examined the awareness, utilisation, and gender disparities in the use of artificial intelligence among secondary school biology students at Lere, Kaduna State. The research was guided by three objectives, three research questions, and one null hypothesis. A descriptive survey research design was adopted, with a population of 18,210 students and a sample size of 375 respondents selected using a multi-stage sampling technique. Data were collected through a structured questionnaire titled AI Awareness and Utilisation in Biology Learning Questionnaire (AIAUBQ), which yielded a reliability coefficient of 0.74, indicating the instrument’s reliability. The data analysis employed mean, standard deviation, and t-test at a 0.05 significance level, using the Statistical Package for Social Sciences (SPSS version 23). The findings revealed a low level of awareness of artificial intelligence tools (ChatGPT and Quillionz) and applications among secondary school biology students in Lere, Kaduna State (mean = 1.91, SD = 0.95). Also, the use of AI tools (ChatGPT and Quillionz) for biology learning is low among secondary school students in Lere, Kaduna State (mean=1.73, SD=0.91), and there is no significant difference in artificial intelligence awareness levels between male and female biology students in secondary schools in Lere, Kaduna State (P=0.09 ˃ 0.05). Based on these findings, it was recommended that the Kaduna state government and NGOs provide essential technological infrastructure to improve access to AI, among other measures.